Single-cell analysis of skin immune cells reveals an Angptl4-ifi20b axis that regulates monocyte differentiation during wound healing - Wee, Jonathan Wei Kiat (2022)
The persistent inflammatory response at the wound site is a cardinal feature of nonhealing wounds. Prolonged neutrophil presence in the wound site due to failed clearance by reduced monocyte-derived macrophages delays the transition from the inflammatory to the proliferative phase of wound healing. Angiopoietin-like 4 protein (Angptl4) is a matricellular protein that has been implicated in many inflammatory diseases. However, its precise role in the immune cell response during wound healing remains unclear. Therefore, we performed flow cytometry and single-cell RNA sequencing to examine the immune cell landscape of excisional wounds from Angptl4+/+ and Angptl4-/- mice. Chemotactic immune cell recruitment and infiltration were not compromised due to Angptl4 deficiency. However, as wound healing progresses, Angptl4-/- wounds have a prolonged neutrophil presence and fewer monocyte-derived macrophages than Angptl4+/+ and Angptl4LysM-/- wounds. The underlying mechanism involves a novel Angptl4-interferon activated gene 202B (ifi202b) axis that regulates monocyte differentiation to macrophages, coordinating neutrophil removal and inflammation resolution. An unbiased kinase inhibitor screen revealed an Angptl4-mediated kinome signaling network involving S6K, JAK, and CDK, among others, that modulates the expression of ifi202b. Silencing ifi202b in Angptl4-/- monocytes, whose endogenous expression was elevated, rescued the impaired monocyte-to-macrophage transition in the in vitro reconstituted wound microenvironment using wound exudate. GSEA and IPA functional analyses revealed that ifi202b-associated canonical pathways and functions involved in the inflammatory response and monocyte cell fate were enriched. Together, we identified ifi202b as a key gatekeeper of monocyte differentiation. By modulating ifi202b expression, Angptl4 orchestrates the inflammatory state, innate immune landscape, and wound healing process.